A PRAGMATIC AND TEXTUAL ANALYSIS OF HUMOR IN THE CAPTION TRANSLATION OF JOHNNY ENGLISH - Tebiyani, Tamara; Baharuddin, Baharuddin; Junaidi, Ahmad (Universitas Islam Sumatera Utara, 2025)
This study examines how captions translate humor in Johnny English, drawing on Mona Baker’s equivalence framework—particularly its textual and pragmatic dimensions. Through analysis of selected scenes, the research shows that captions convey meaning not only through linguistic transfer but also by integrating visual cues, sound effects, and comedic timing. Textual equivalence is analyzed in terms of cohesion, coherence, and dialogue sequencing, while pragmatic equivalence addresses implicit meaning, cultural references, and humor reception. The findings reveal that captioning often departs from literal translation to apply pragmatic adjustments, ensuring that irony, slapstick, and parody remain effective for target audiences. Textual strategies such as omission, condensation, and sequencing help preserve narrative flow and comedic rhythm. Overall, the study underscores captions as sites of creative negotiation between fidelity and functionality, reaffirming the relevance of Baker’s equivalence model in audiovisual translation.